2018
DOI: 10.1039/c8py01287c
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetism in two-dimensional polyradical nanosheets

Abstract: 2D polyradical nanosheets were prepared using interfacial polymerization and exhibited obvious antiferromagnetic behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…We consider three examples of TAM‐based 2D hex‐CORFs based on: a) ring‐sharing (rs) triphenylmethyl (TPM) radicals [ 9 ] ‐ TPM rs , b) ring‐sharing perchlorotriphenylmethyl (PTM) radicals [ 9 ] ‐ PTM rs , and c) acetylenic linked PTM radicals as found in a recently synthesized and experimentally characterized material (PTM acetylenic ) [ 10,11 ] (see Figure ). We note that although TPM rs and PTM rs have not yet been synthesized as extended materials, recently, it has been experimentally demonstrated that one can connect TPMs via ring‐sharing in molecules containing a ring of six αC centers (i.e., a TPM rs fragment).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider three examples of TAM‐based 2D hex‐CORFs based on: a) ring‐sharing (rs) triphenylmethyl (TPM) radicals [ 9 ] ‐ TPM rs , b) ring‐sharing perchlorotriphenylmethyl (PTM) radicals [ 9 ] ‐ PTM rs , and c) acetylenic linked PTM radicals as found in a recently synthesized and experimentally characterized material (PTM acetylenic ) [ 10,11 ] (see Figure ). We note that although TPM rs and PTM rs have not yet been synthesized as extended materials, recently, it has been experimentally demonstrated that one can connect TPMs via ring‐sharing in molecules containing a ring of six αC centers (i.e., a TPM rs fragment).…”
Section: Resultsmentioning
confidence: 99%
“…[ 8,9 ] Since our prediction, some example 2D CORFs have been experimentally prepared. [ 10–12 ] Herein, we focus on 2D CORFs with hexagonal connectivity based on the graphene‐like honeycomb lattice (2D hex‐CORFs), which we predicted to exhibit spin‐polarized antiferromagnetic (AF) ground states and low energy valence bond quinoidal gapped states, linked by an intervening semimetallic transition state. [ 9 ] Compared to the delocalized semimetallic state, the more stable AF and valence bond states have lower space group symmetries and thus can be described as emerging through symmetry breaking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 There it has been shown that, in order to obtain a tunable electron pairing at room temperature via dihedral angle manipulation, the aC centres should be separated by a single aryl ring, 36 in line with previously reported trends for TAM dimers. 9,21 On the contrary, TAM 2D-COFs where radical centres are further away from each other, such as the recently synthesized materials, [45][46][47] show a persistent multi-radical conguration that is insensitive to aryl ring attening. 36 Based on these ndings, here we consider ring-sharing p-TAM polymers (Fig.…”
Section: Materials Designmentioning
confidence: 95%
“…FM 26 28 or AFM 29 ) and diamagnetic quinoidal closed-shell solutions 30 , confirming that the electronic bi-stability from the bi-radical monomers persists in the resulting 2D materials. Recently, different examples of experimentally synthesised 2D-CORFs have been reported, exhibiting multi-radical electronic ground states with either AFM coupling 31 , 32 or weak coupling (i.e. paramagnetism) between spins 33 .…”
Section: Introductionmentioning
confidence: 99%